"Sans Titre" : 4 Années d'Acquisition au Musée de Toulon. - Bazzoli, François; Beaud, Marie-Claude; Bombert, Daniel; Caujolle, Christian; Coulomb, Guillemette (Toulon : Musée de Toulon, 1982)
Africano, Nicholas ; Aillaud, Gilles ; Alechinsky, Pierre ; Asse, Geneviève, Asse ; Bacon, Francis ; Baljeu, Joost ; Bazile, Bernard ; Vautier, Ben ; Bill, Jakob ; Bill, Max ; Blake, John ; Bonies, Bob ; Bryen, Camille ; Cahn, Marcelle ; calder, Alexandre ; Candolfi, Serge ; etc.
"Sans Titre" : 4 Années d'Acquisition au Musée de Toulon, 16 juillet - 30 septembre 1982
Frans
kunstcatalogus